Expression Of CK19 Gene In Patients With Lung Cancer And Its Comparison With Carcinoembryonic Antigen In Peripheral Blood - Abdolreza Mohamadnia; Shirin Karimi; Reza Yadegar Azari; Seyed Alireza Naji; Adnan Khosravi; Naghmeh Bahrami; Massoud Saidijam (Tehran University of Medical Sciences, 2016)
Background and Aim: Lung cancer is the most common cancer among men around the world. The aim of this study was to determine the expression levels of CK19 mRNA marker in the affected patients’ peripheral blood. Materials and Methods: Thirty patients with lung cancer (NSCLC type) were compared with 30 healthy controls. After taking peripheral blood samples and extracting total RNA, cDNA was synthesized and examined by Real-time RT-PCR technique. Then, the CEA antigen was measured by ELISA. Results: The CK19mRNA was positive in 7 out of 30 lung cancer patients. Hence, its sensitivity was determined to be 23.3 %. The serum level of CEA antigen was positive in 11 out of 30 lung cancer patients. The mean serum level of CEA antigen markers was higher in patients than in controls; the difference was statistically significant (P< 0.001). The sensitivity of this test was determined to be 36.6 %. Conclusion: This study showed that the sensitivity of CK19 mRNA in peripheral blood was low, but it had a high specificity for the diagnosis of primary lung cancer. Also, it was found that CEA antigen could be the specific marker for the early detection of lung cancer in patients’ peripheral blood.